La mediación como solución en asuntos laborales - Loor Santana, Jaime Miguel (2015)
Mediation is a means of conflict resolution that would help solve their problems based on their own ways of seeing things. The objects of study constitute court proceedings. The project addresses the issue of the need to implement mediation to resolve disputes in a friendly manner avoiding conflict and tension-filled form of judicial process. It should change the paradigm of a culture of violence, one that promotes a culture of peace. Therefore, the spread of mediation and other Alternative Means of Dispute Resolution so that they can use in their various problems is necessary. The purpose is to seek a mediated in an environment friendly solution. The lack of mediation is necessary to seek more outreach to benefit society in conflict mediation centers set up in the country; the new vision of the conflict; and Alternative Means of Dispute Resolution used in Ecuador. The procedure using the methodology known design used to validate the instrument of this research, reaching conclusions and recommendations that will allow to know the importance of using mediation as an alternative method to resolve conflicts is unknown that right by citizens and citizens, building a new paradigm in their lives where prevails the will of the parties to a conflict.